A new insight into the beta′′′ structure: Three categories of configurations between beta′ precipitates in aged binary Mg-Nd alloy. (November 2019) - Tan, J.; Dong, Y.; Zhang, H.X.; Sun, Y.H.; Sun, B.Z.; Qi, Y.
Abstract: The morphology and the structure of β F ′ metastable phase were studied in aged binary MgNd alloy by atomic-resolution scanning transmission electron microscopy (STEM). The proposed three categories of β F ′ −  β F ′ configurations are respectively aligned, staggered and inserted configurations, which can explain well the β ′′′ structure proposed previously based on the experimental images and constructed models. The inserted β F ′ −  β F ′ configuration is the most important one during the structural evolution of aging, which play a crucial role in the in-situ transformation from the D 019 -like to the quasi- β 1 structures. Graphical abstract: According to experimental images and constructed models, the proposed three types of β F ′ −  β F ′ configurations are as follows: Aligned β F ′ −  β F ′ configuration–I, staggered β F ′ −  β F ′ configuration–II and inserted β F ′ −  β F ′ configuration–III including partial and full inserted types.Unlabelled Image